Graphitic carbon nitride-based materials for photoelectrochemical water splitting - Kumar U.; Sinha I. (My University, 2025)
Graphitic carbon nitride is a potential metal-free option for fabricating photoanodes in photoelectrochemical cells. This chapter concentrates on different thin film forms of g-C3N4, its composites, and doped g-C3N4. It lists the preparation techniques for bulk g-C3N4 and the effect of varying the parameters on its properties. The disadvantages of g-C3N4 films prepared by top–down methods are enumerated. Different bottom–up techniques for fabricating g-C3N4 photoelectrode films are discussed, along with their advantages. Doped and g-C3N4 thin film-based heterostructure photoelectrodes and their activities are also described. The last section of the chapter gives the properties of surface-modified g-C3N4 thin films. © 2024 Elsevier Ltd. All rights reserved.